ANALYSIS OF EQUITY AND ITS EFFICIENCY IN JOINT STOCK COMPANIES OF UZBEKISTAN - Bunyod Usmonov (Scholar Express Journals, 2023)
In the article, the relevance of the research is based on the existing problems in the assessment of capital efficiency in companies, and the theoretical basis for increasing equity efficiency is highlighted. Also, an analysis was carried out to evaluate the capital efficiency of joint stock companies operating in our country. Based on the results, conclusions and recommendations on increasing capital efficiency have been developed
Keywords: Equity, assessment, management, efficiency, capital management, analysis